Planning of the Ergonomic Seat for Four Wheel Tractor Based on Anthropometry - Hidayah, Titik Nur; Lutfi, Musthofa; Anam, Khoirul (Jurnal Teknologi Pertanian, 2010)
Seat is a dominant factor in increasing the healthy and safety for four-wheel tractor operator. Â Therefore it is needed to be designed to suit the Indonesian people bodyâs dimension in general. This study was done to measure the bodyâs dimension of 100 students at the age of 19 to 30 years old. The data collected from this sample were: genuflection height data, shoulderâs height to sitting position data, pelvis width data, the distance of genuflection to the base data, the distance of the curve central point of vertebrate, and the weight of body in sitting position. The result of this study shows that: the present height of tractor seat base is 35 cm, while the proposed height is 39 cm. The present length of seat base is 34 cm while the proposed length is 51 cm. The present width of the seat base is 34 cm while the proposed width is 41 cm. The present height of back of the seat is 27 cm while the proposed height is 64 cm. The present width of back of the seat is 40 cm while the proposed width is 50 cm. The proposed curved of the back is 33 cm. The load can be resisted is 53 kg. Keywords: anthropometrics, tractor, ergonomic